Climate Change and Human Rights: the First Cases Before the European Court of Human Rights - Keturakienė, Airė; Murauskas, Donatas (Teisė, 2023)
We analyse applications presented to the European Court of Human Rights raising the issue of insufficient actions of States to fight climate change. First, we discuss the relevant national cases that expose three different approaches towards climate change justice cases, i.e. the cases from the Netherlands, Norway, and Germany. Second, considering the European Court of Human Rights criteria on inadmissibility and substance, we assess major issues related to the presented applications and their success.